MUSTAFA ŞEKİP TUNÇ'S LIFE, WORKS AND "THE EFFECTS OF TURKISH REVOLUTION TO PHILOSOPHY" ARTICLES IN HAYAT JOURNAL - Abdimitalip uulu, Nursultan (Scientific Journal of Faculty of Theology, 2012)
Tlris article aim at a recognition about one of Turkish Revulution's important brain, Mustafa Şekip Tunç and his Works in the Turkish Assia. Also including Mustafa Şekip's "The effects of Turkish Revolution to Philosophy" article's translated from Ottoman Language to Turkish.